Analysis of Service Quality on the Best Hotels in Kalimantan Based on Booking.com Website - Nugraha, Rizki Nurul (Westscience Press, 2024)
A hotel must certainly provide the best service in order to provide a satisfying and pleasant experience for guests. If the quality of service provided is not satisfactory for guests, it will get negative feedback, so that the image of the hotel decreases. This study aims to analyze the quality of service at the best hotels in Kalimantan based on guest reviews from Booking.com website. This type of research is qualitative, with qualitative descriptive analysis methods. Data collection was carried out by observing guest reviews in the top 5 hotels from the list of the best hotels in Kalimantan based on the website Booking.com The results showed that the analysis of the service quality of the five best hotels in Kalimantan based on Booking.com website, what needs to be considered is the quality of cleanliness, staff service, guest comfort, adequate facilities, and strategic location are the added points of the hotel.